2005
DOI: 10.1007/s10388-005-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiotherapy and surgery for locally advanced esophageal basaloid squamous carcinoma: report of successful

Abstract: A 58-year-old Japanese man complained of dysphagia, and esophagography and endoscopy showed a 7.5-cm-long protruding tumor in his middle esophagus. Biopsy diagnosed the lesion as basaloid squamous carcinoma. We assessed the tumor as T3N0M0 stage II. Preoperative chemoradiotherapy was started, consisting of 3 weeks of intravenous chemotherapy with 10 mg/day cisplatin and 750 mg/day 5-fluorouracil and concurrent total 45-Gy external irradiation applied to the tumor. We evaluated the effectiveness as a partial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
3

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
1
0
3
Order By: Relevance
“…Previous studies have reported that patients with early-stage BSC and those who undergo curative resection can be expected to have outcomes similar to those of patients with typical squamous cell carcinoma (SCC) of the esophagus [6,7]. Some of these patients respond to chemotherapy [4,5,8]. Early detection and multidisciplinary therapy are essential for improved outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have reported that patients with early-stage BSC and those who undergo curative resection can be expected to have outcomes similar to those of patients with typical squamous cell carcinoma (SCC) of the esophagus [6,7]. Some of these patients respond to chemotherapy [4,5,8]. Early detection and multidisciplinary therapy are essential for improved outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…O paciente apresentou acentuada queda do estado geral e evoluiu para óbito com quadro de melena, quatro meses após o diagnóstico. , o carcinoma basalóide escamoso é mais freqüente em homens com idade acima de 40 anos e no terço médio do esôfago torácico 2,4,5,13 . Tais características sobrepõem-se às observadas no presente caso, exceto para o local da lesão, que estava situada no terço distal do esôfago, coincidindo com o referido por Albuquerque et al (2006) .…”
Section: Relato Do Casounclassified
“…Autores japoneses preconizam quimioterapia com 5-Fluoracil e cisplatina para os tumores localmente avançados, sem metástases à distância 4,7 . Esta conduta visa reduzir as dimensões da lesão primária, de modo a viabilizar a realização da esofagectomia associada a linfadenectomia em três campos: cervical, torácico e abdominal, com razoável índice de sobrevida.…”
Section: Relato Do Casounclassified
See 1 more Smart Citation